2011
DOI: 10.1111/j.1365-2621.2010.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of isolated flaxseed mucilage as a non‐starch polysaccharide on noodle quality

Abstract: Physicochemical, cooking quality and sensory characteristics of noodles enriched by extracted flaxseed mucilage were evaluated. Noodles were prepared with replacement wheat flour with different mucilage concentrations and drying at different temperatures. Generally, physicochemical and noodle quality characteristics improved with adding flaxseed mucilage compared to control sample. The correlation between optimum cooking time with mucilage concentrations and drying temperatures established by nonlinear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The lowest cooking loss was found with the addition of CMC (Fig. 1d) because an electrostatic complex with gluten proteins was formed by the addition of CMC that increased the gluten network strength and reduced the cooking loss (Kishk et al 2011).…”
Section: Resultsmentioning
confidence: 98%
“…The lowest cooking loss was found with the addition of CMC (Fig. 1d) because an electrostatic complex with gluten proteins was formed by the addition of CMC that increased the gluten network strength and reduced the cooking loss (Kishk et al 2011).…”
Section: Resultsmentioning
confidence: 98%
“…The T 4 KGM noodle samples showed the least cooking loss. During the cooking of noodle in water, some soluble components including amylose (the principle component), non-starch polysaccharides and protein escape from the network during starch granule gelatinization, due to a weak or discontinuous gluten matrix (Kishk et al 2011). It showed that large KGM substitution of wheat flour at the start of dough mixing increased the cooking loss of noodle samples, suggesting that a greater amount of exudates escaped from the dough system during starch granule gelatinization.…”
Section: Effects Of Kgm On Cooking Propertiesmentioning
confidence: 99%
“…bread, noodles, muffin, biscuits, cookies, dairy products) as ground axseed, axseed oil, axseed mucilage or as axseed hulls to improve the nutritional quality of foods. [14][15][16][17][18][19][20][21][22] Flaxseed affects the quality characteristics of these products. 14,23,24 Previous studies have reported effect of axseed addition on the avor prole, antioxidant, nutritional and other characteristics of different food products.…”
Section: Introductionmentioning
confidence: 99%